Pathological effect of infectious bronchitis disease virus on broiler chicken trachea and kidney tissues - Hasan, Ismael I. (Vet World, 2020)
AIM: This study aimed to investigate the pathological effects of the infectious bronchitis virus (IBV) on chicken trachea and kidney tissues and also desired to diagnose the virus genome using a molecular tool. MATERIALS AND METHODS: Twenty trachea and kidney samples collected from one broiler farm contain 10,000 chickens at Tikrit city. The chickens showed signs of gasping and mortality (20%) at early ages (20 days old), the presence of IBV investigated using conventional reverse transcriptase-polymerase chain reaction technique with routine histopathological study to tracheal and renal tissue. RESULTS: Postmortem lesion showed severe respiratory inflammation with abscesses at tracheal bifurcation lead to airway blog. Molecular results showed two genotypes of IBV, one of them not included in primer designer research. The histological study showed different stages of inflammation, degeneration, and necrosis to the renal and tracheal tissues. CONCLUSION: The respiratory and renal pathological effect of the virus responsible for the symptoms appeared on the affected chicks that caused mortality, with a high probability of presence of a new viral genotype added to the untranslated region.